Tax Competition as a Challenge to the Governance of Global Economy - Penttilä, Seppo; Kultalahti, Jukka (European Spatial Research and Policy, 2013)
The paper analyses the role of tax competition in global economy. How can tax systems respond to the challenge – by international cooperation or by national rules, by tax harmonisation or by tax competition? In this paper we approach the question as a matter of global governance. Tax competition is seen both as a means and as an object of global governance. Our conclusion is that there is no universal answer to the question: competition or harmonisation? Attempts to govern the processes of global economy on a national level may easily lead to tax competition. On the other hand, at least at the supranational level, i.e. at regional or global level, the goals and mechanisms of governance seem to emphasise harmonisation. Nowadays especially the OECD has become an important actor or forum for cooperation in taxation. It has succeeded in many ways in preventing and reducing harmful tax competition. The soft law mechanisms developed by the OECD have often been converted into the hard law mechanisms on national level. The governance activities have been based on both soft law and hard law mechanisms.